2013
DOI: 10.1242/jeb.081802
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular design in fin whales: high-stiffness arteries protect against adverse pressure gradients at depth

Abstract: SUMMARYFin whales have an incompliant aorta, which, we hypothesize, represents an adaptation to large, depth-induced variations in arterial transmural pressures. We hypothesize these variations arise from a limited ability of tissues to respond to rapid changes in ambient ocean pressures during a dive. We tested this hypothesis by measuring arterial mechanics experimentally and modelling arterial transmural pressures mathematically. The mechanical properties of mammalian arteries reflect the physiological load… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 65 publications
1
23
0
Order By: Relevance
“…The cardiovascular adaptations of the marine mammals allow for the diving habits. Among these adaptations, an expansive ascending aorta or an expansive aortic arch and a non-compliant or low compliant descending aorta have been described (Drabek, 1975;Lille, Piscitelli, Volg, Gosline, & Shadwick, 2013;Melnikov, 1997;Shadwick & Gosline, 1994, 1995. These characteristics are considered the aortic adaptations of some marine mammals for diving.…”
mentioning
confidence: 99%
“…The cardiovascular adaptations of the marine mammals allow for the diving habits. Among these adaptations, an expansive ascending aorta or an expansive aortic arch and a non-compliant or low compliant descending aorta have been described (Drabek, 1975;Lille, Piscitelli, Volg, Gosline, & Shadwick, 2013;Melnikov, 1997;Shadwick & Gosline, 1994, 1995. These characteristics are considered the aortic adaptations of some marine mammals for diving.…”
mentioning
confidence: 99%
“…Other biological materials are known to similarly specialize in either compression (mammalian bone, Reilly and Burstein , cetacean heart valves, Lillie et al. ) or tension (mussel byssus, Bell and Gosline , aquatic plants, Etnier and Villani ). Future work should examine the histological differences that may exist between Nereocystis pneumatocyst tissue, which resists compression, and Nereocystis stipe tissue, which is known to resist tension (Johnson and Koehl , Denny et al.…”
Section: Discussionmentioning
confidence: 99%
“…subsequent study byLillie et al 2013 found that, with the exception of a few arteries right off the arch 371 that had the same high distensibility as the arch, all the other arteries examined from a fin whale 372…”
mentioning
confidence: 93%
“…The model described by Lillie et al 2013 predicted that transient differences between thoracic and 466 ambient pressure will develop during the descent and ascent portion of a dive, and that the gradients 467 can eventually be ameliorated by a shift in blood volume, possibly into the thoracic retia or aortic arch. If 468 these predictions prove accurate, the arteries must experience a wider range of transmural pressures 469 than normally associated with mammalian circulation, making the absence of compliance in the 470 peripheral arteries a possible adaptation to deal with these pressure effects.…”
mentioning
confidence: 99%
See 1 more Smart Citation